Pemikiran Muhammad Mansur Tentang Imk?n al-Ru’yah dalam Kitab Mîz?n al-I’tid?l - Asshidiqi, Iqnaul Umam; Rausi, Fathor (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2021)
Abstract Imk?n al-ru’yah is a method which compromises between reckoning and observation. The development of discourse imk?n al-ru’yah always create a variety of criteria limits. Long before the existence of various criteria limits in the world of current astronomy, Sayyid Usman has proposed the existence of 7° imk?n al-ru’yah criteria. Sayyid Usman's criteria received a serious response from Muhammad Mansur as outlined in the book Mîz?n al-I’tid?l. This research is intended to answer these problems: (1) What is the background of Muhammad Mansur's thinking about imk?n al-ru’yah? (2) What is the perspective of astronomy towards Muhammad Mansur's imk?n al-ru’yah? These problems are discussed using a qualitative type of library research. The Book of Mîz?n al-I’tid?l is used as the primary source in this study which is supported by other sources as secondary sources. The collection of data in this study uses method of documentation and interviews. Next, the data is analyzed using critical analytic descriptive. The results of this study indicate that Muhammad Mansur's thinking background on imk?n al-ru’yah was influenced by his father, Abdul Hamid, who incidentally was one of Abdurrahman al-Misri's students. Astronomically, the thought of Muhammad Mansur's imk?n al-ru’yah is dynamic and naturalistic. Keywords : Crescent Visibility, Muhammad Mansur, Mîz?n al-I’tid?l.